Mengembangkan Kecerdasan Majemuk pada Generasi Milenial Siswa Sekolah Dasar Islam Terpadu (SDIT) Insantama Malang - Retno Sulistiyaningsih; Nur Eva; Nur Rohmah Hidayatul Qoyyimah; Najway Azka Ar-Robbaniy; Sri Andayani (Universitas Nurul Jadid, 2020)
Multiple intelligence is one way to understand the abilities possessed by children. This needs to be re-understood considering that many parents see intelligence based solely on report card scores. It is important to provide understanding to parents about multiple intelligence in order to understand the conditions of development and intelligence possessed by their children. This research aims to increase parents's knowledge about multiple intelligences. This study used a quantitative approach with a quasi-type experiment through the provision of psychoeducation. The subjects in this study were 11 parents of SDIT Insantama Malang students with various educational and occupational backgrounds. The study used the Guttman scale to collect data. Participants received a pre-test and post-test to determine the differences before and after attending psychoeducation. Data analysis used paired t test as statistical analysis. The result of this study is that there is a significant influence on the increase in the knowledge of parents about multiple intelligence with a significance value of 0.00 and a t value of -12,111.